Innovation in technical backstopping for the thiruvanthapuram district panchayat-A critical appraisal of the samagra project on banana cultivation - Esakkimuthu M (Department of Agricultural Extension, College of Agriculture, 2012)
Poverty eradication is a long term goal of India. Since independence a number of poverty alleviation programmes including agricultural developmet programmes were launched. It would be incorrect to say that all the poverty alleviation programmes had shown the results much expected. In this way, the ‘Samagra’ project on Banana cultivation is a flagship project with multistakeholer partnerships in Kerala. It was launched in 2007 by the Thiruvananthapuram District Panchayat and Kudumbashree Mission, with the aim of enhancing banana productivity through the promotion of innovations in technical backstopping. The study entitled “Innovations in technical backstopping for the Thiruvananthapuram District Panchayat – A critical appraisal of the ‘Samagra’ project on banana cultivation” is an attempt to explore the innovations in technical backstopping measured in terms of perception about the innovative procedures, processes and institutions of the ‘Samagra’ Project. The study was conducted in three Grama Panchayats of Thiruvananthapuram district namely ., Kottukal, Kunnathukal and Kalliyoor. Simple random sampling technique was followed in the selection of Block Panchayats, Grama Panchayats beneficiaries. Three categories of respondents namely beneficiary respondents, implementing officials and people’s representatives were involved in the study. Sixty beneficiary respondents, thirty implementing officials and thirty people’s representatives were selected. Thus, the total number of respondents for the study was 120. The dependent variable innovations in technical backstopping was measured in terms of perception about the innovative procedures, processes and institutions. The profile characteristics of the respondents such as age, area under cultivation, experience in banana cultivation, annual income, educational status, cosmopoliteness, social participation, trainings attended, information need perception, credit orientation, risk orientation, economic motivation. Innovativeness, achievement motivation and attitude towards ‘Samagra’, and the constraints were studied using scientific procedures. The major findings of the study indicate that majority of the beneficiary respondents rated that innovative procedures adopted in the ‘Samagra’ project were excellent and all the officials and people’s representatives also had excellent appreciation of the innovative procedures adopted in the ‘Samagra’ project. Regarding the perception of innovative processes, majority of the beneficiary- respondents, implementing officials and people’s represenatives opined that innovative procedures adopted in the ‘Samagra’ project were excellent. The perception about the innovative institutions was also appreciable in respect of all the three groups of respondents. The findings regarding the attitude of beneficiary respondents revealed that, 60 per cent of the respondents had favourable attitude towards ‘Samagra’ of which 40 per cent were having neutral attitude. 93.3 per cent of the implementing officials had favourable attitude and 6.7 per cent had neutral attitude towards ‘Samagra’. 60 per cent of the people’s representatives had favourable attitude and 40 per cent had neutral attitude towards ‘Samagra’. Results of the correlation between the independent and dependent variables of respondents revealed that among the selected thirteen independent variables namely experience, education, credit orientation, economic motivation and achievement motivation showed positive significant relationship with innovative procedures, processes and institutions.